Experimental Cross-Species Transmission of Rat Hepatitis E Virus to Rhesus and Cynomolgus Monkeys - Fengmei Yang; Yanyan Li; Yongjie Li; Weihua Jin; Suqin Duan; Hongjie Xu; Yuan Zhao; Zhanlong He; Yasushi Ami; Yuriko Suzaki; Yen Hai Doan; Naokazu Takeda; et al. (Viruses, 2022)
Rat hepatitis E virus (rat HEV) was first identified in wild rats and was classified as the species Orthohepevirus C in the genera Orthohepevirus, which is genetically different from the genotypes HEV-1 to HEV-8, which are classified as the species Orthohepevirus A. Although recent reports suggest that rat HEV transmits to humans and causes hepatitis, the infectivity of rat HEV to non-human primates such as cynomolgus and rhesus monkeys remains controversial. To investigate whether rat HEV infects non-human primates, we inoculated one cynomolgus monkey and five rhesus monkeys with a V-105 strain of rat HEV via an intravenous injection. Although no significant elevation of alanine aminotransferase (ALT) was observed, rat HEV RNA was detected in fecal specimens, and seroconversion was observed in all six monkeys. The partial nucleotide sequences of the rat HEV recovered from the rat HEV-infected monkeys were identical to those of the V-105 strain, indicating that the infection was caused by the rat HEV. The rat HEV recovered from the cynomolgus and rhesus monkeys successfully infected both nude and Sprague-Dawley rats. The entire rat HEV genome recovered from nude rats was identical to that of the V-105 strain, suggesting that the rat HEV replicates in monkeys and infectious viruses were released into the fecal specimens. These results demonstrated that cynomolgus and rhesus monkeys are susceptible to rat HEV, and they indicate the possibility of a zoonotic infection of rat HEV. Cynomolgus and rhesus monkeys might be useful as animal models for vaccine development.